Dolomitization of the Middle Jurassic limestones at the Vajont Canyon (Southern Alps, Italy): Fault-controlled dolomitization by hypo-to mesosaline fluids. (October 2022) - Mozafari, Mahtab; Swennen, Rudy; Storti, Fabrizio; Cortinovis, Silvia; Lauriks, Katherine; Balsamo, Fabrizio; Bistacchi, Andrea; El Desouky, Hamdy; Taberne, Conxita
Abstract: The Middle Jurassic limestones of the Vajont Formation, which constitute major parts of the flanks of the Vajont Canyon (Southern Alps, Italy), have been subjected to pervasive dolomitization. The dolomites are localized within fault damage zones. Based on field and petrographic characteristics, two dolostone groups can be differentiated. Group 1, being the most prevailing, corresponds to replacive matrix dolostones. They form non-stratabound plume-like geobodies. They also occur as infill in infrequent veins in the host limestones that occur adjacent to these replacive plume-like dolostone bodies. Group 2, that is less common, consists of saddle dolomite cements. It occurs in breccia and veins or makes up zebra dolostones. The latter cements frequently affect the replacive group 1 dolostones. Fluid inclusion analyses of both dolostone groups indicate comparable salinity values of 1.2–5.3 eq. wt.% NaCl with homogenization temperatures of 70–108 °C, which in addition of overlapping 87 Sr/ 86 Sr ratios (0.70811–0.70846) reflect similar parental fluids. The estimated salinities, in combination with δ 18 O values (−5.5 to −14.8‰ V-PDB), indicate significant contributions of 18 O-depleted fluids postulated to be modified meteoric waters. This origin is supported by the low trace element contents measured in the studied dolostones. These data support that the fault-controlled dolostones in the studied Vajont area precipitated from hot hypo- to mesohaline fluids. These fluids could have circulated along inherited Mesozoic syn-rift fault and fracture corridors. However, another possibility is that fluids circulated along fault and fracture systems that developed during the Neo-Alpine Orogeny (Miocene). Both could have served as efficient deep-seated fluid migration conduits as well as relatively shallow ones facilitating the downward flow of topography-driven meteoric waters. Highlights: Dolomitization by hypo-to mesosaline fluids. Likely candidate to deliver the dolomitizing fluids is the Upper Triassic Dolomia Principale. Two similar dolomitization pulses were differentiated with similar salinity, stable carbon and oxygen and Sr 87 /Sr 86 signatures. Porosity enhancement occurred by dolomitization, while porosity reduction was recognized to be caused by over-dolomitization.